2019
DOI: 10.1001/jama.2019.15468
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lefamulin vs Moxifloxacin for Early Clinical Response Among Adults With Community-Acquired Bacterial Pneumonia

Abstract: IMPORTANCE New antibacterials are needed to treat community-acquired bacterial pneumonia (CABP) because of growing antibacterial resistance and safety concerns with standard care.OBJECTIVE To evaluate the efficacy and adverse events of a 5-day oral lefamulin regimen in patients with CABP. DESIGN, SETTING, AND PARTICIPANTSA phase 3, noninferiority randomized clinical trial conducted at 99 sites in 19 countries that included adults aged 18 years or older with a Pneumonia Outcomes Research Team (PORT) risk class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 15 publications
0
98
0
9
Order By: Relevance
“…Diarrhea was less common with IV lefamulin compared to moxifloxacin (1 vs 8%), yet more common in LEAP-2 with the oral formulation (12% vs 1%), The rationale for this large difference is currently unknown. Hepatic enzyme elevations, nausea, hypokalemia, insomnia, and headache occurred with both formulations of lefamulin at rates similar to those with moxifloxacin [47]. In the Phase II ABSSSI trial, more headache, nausea, infusion site phlebitis, and pruritus were observed in the vancomycin arm when compared to the lefamulin arms, although statistical significance was not noted [48].…”
Section: Safety Pregnancy and Lactationmentioning
confidence: 95%
See 3 more Smart Citations
“…Diarrhea was less common with IV lefamulin compared to moxifloxacin (1 vs 8%), yet more common in LEAP-2 with the oral formulation (12% vs 1%), The rationale for this large difference is currently unknown. Hepatic enzyme elevations, nausea, hypokalemia, insomnia, and headache occurred with both formulations of lefamulin at rates similar to those with moxifloxacin [47]. In the Phase II ABSSSI trial, more headache, nausea, infusion site phlebitis, and pruritus were observed in the vancomycin arm when compared to the lefamulin arms, although statistical significance was not noted [48].…”
Section: Safety Pregnancy and Lactationmentioning
confidence: 95%
“…With potent activity against CABP pathogens and high pulmonary concentrations, lefamulin demonstrates antimicrobial properties ideal for respiratory tract infections. The Lefamulin Evaluation Against Pneumonia (LEAP)-1 and -2 studies were similarly designed multicenter randomized controlled trials that tested non-inferiority of lefamulin against moxifloxacin in adults with CABP [46,47]. Study details and comparisons of population characteristics and endpoints are in Tables 2 and 3.…”
Section: Community-acquired Bacterial Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…38 The LEAP 2 study compared the safety and efficacy of oral lefamulin twice daily for 5 days versus oral moxifloxacin once daily for 7 days in 738 adult patients with moderate CAP, and also demonstrated non-inferiority between the two therapeutic options. 39 On August of 2019, based on the results of these trials, the FDA announced the approval of lefamulin for the treatment of CAP. 40 Despite this approval the ATS and the IDSA demand further validation in the outpatient setting.…”
Section: Lefamulinmentioning
confidence: 99%